Designing Stable Radicals with Highly Electrophilic or Nucleophilic Character: Thiadiazinyl as a Case Study. Issue 3 (11th December 2014) - De Vleeschouwer, Freija; Chankisjijev, Artiom; Geerlings, Paul; De Proft, Frank
Abstract: Theoretical design can be an important aid in the discovery of valuable stable radical systems. In this study, inverse molecular design was applied to thiadiazinyl radicals to maximize two fundamental electronic properties in chemistry, namely electrophilicity and nucleophilicity. We discovered that the thiadiazinyl structure can be made moderately nucleophilic or highly electrophilic, depending on the electronic character of its substituents. The most electrophilic thiadiazinyl radical displays the highest electrophilic character encountered so far for uncharged radical systems. The accumulated data relating to the influence of different substituents at the various sites has allowed us to propose thiadiazinyl radicals that are intrinsically stable and as electrophilic or nucleophilic as possible. Although the nucleophilicity optimum fulfills the additional requirement of being stable, a significant drop from highly to merely moderately electrophilic is observed for the new electrophilicity optimum. Abstract : Inverse molecular design has revealed that the thiadiazinyl structure can be made moderately nucleophilic or highly electrophilic depending on the electronic character of its substituents. Under the additional condition of being stable, the electrophilicity optimum shows a significant drop from highly to merely moderately electrophilic.